Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1046/j.1365-3040.2003.00968.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcript levels of AtMRPs after cadmium treatment: induction of AtMRP3

Abstract: In yeasts, the ABC-type transporters are involved in vacuolar sequestration of cadmium. In plants, transport experiments with isolated vacuoles indicate that this is also true. In order to know more about the response of AtMRPs, a subclass of Arabidopsis ABC transporters, to cadmium, their expression pattern was analysed using the microchip technology and semi-quantitative reverse transcriptasepolymerase chain reaction. From 15 putative sequences coding for AtMRPs, transcript levels were detected for 14. All w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(77 citation statements)
references
References 57 publications
(101 reference statements)
4
73
0
Order By: Relevance
“…In the yeast, ABC transporters are involved in the vacuolar sequestration of Cd (Ortiz et al 1992;Wemmie et al 1994). Bovet et al (2003) studied the expression of several AtMRP genes in Cd-exposed A. thaliana. The expression of four genes, including AtMRP4 and AtMRP10, was up-regulated exclusively in the roots where Cd is retained, but expression was also found in the shoots.…”
Section: Discussionmentioning
confidence: 99%
“…In the yeast, ABC transporters are involved in the vacuolar sequestration of Cd (Ortiz et al 1992;Wemmie et al 1994). Bovet et al (2003) studied the expression of several AtMRP genes in Cd-exposed A. thaliana. The expression of four genes, including AtMRP4 and AtMRP10, was up-regulated exclusively in the roots where Cd is retained, but expression was also found in the shoots.…”
Section: Discussionmentioning
confidence: 99%
“…Only one protein, an MRP-like ABC transporter, exhibited an increased protein ratio in the low and high Cd 2+ experiments. Interestingly, this MRP exhibits the highest homology to AtMRP3, the Arabidopsis MRP, which responds most strongly to Cd 2+ treatment in Arabidopsis [17]. AtMRP3 partially restores Cd 2+ tolerance in a Cd 2+ -sensitive yeast, suggesting that it is involved in vacuolar Cd 2+ transport.…”
Section: Atmrp3 Is Upregulated Under Low and High CD 2+mentioning
confidence: 97%
“…Cd 2+ was extracted by a 1.8 M H 2 SO 4 treatment and analyzed as described [17]. To determine Cd 2+ content in the growth substrates, 50 g of Vermiculite was centrifuged at 3000 g for 10 min.…”
Section: Determination Of Free CD 2+mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated that ABC transporters could be involved in cadmium efflux, transport, sequestration and ⁄ or redistribution (Bovet et al, 2003(Bovet et al, , 2005Kim et al, 2007). The P-type ion pump HMA4 has been studied extensively (Verret et al, 2004(Verret et al, , 2005Mills et al, 2005;Talke et al, 2006;Courbot et al, 2007;Hanikenne et al, 2008).…”
Section: Researchmentioning
confidence: 99%